From chronicle to canon: the hermeneutics of the Spring and autumn, according to Tung Chung-shu - Queen, Sarah A. (Cambridge studies in Chinese history, literature, and institutions, 1996)
Every general account of the development of Chinese thought makes mention of Tung Chung-shu (c. 195–105 bce) as one of the pivotal philosophers of the Han. Professor Queen's accomplishment is a meticulous dissection of Tung Chung-shu's major work. The Luxuriant Gems of the Spring and Autumn Annals (Ch'un-ch'iu fan lu) established the first state-sponsored Confucian Canon, and created an ideal of the ruler and his role in government that was central to political discussion for two thousand years. The author has carefully scrutinised this text for authenticity, and has concluded that it was compiled several centuries after Tung's death, but was mostly compiled from Tung's authentic writings. By historicising this important text, Queen allows a new view of Tung's relation to the political and doctrinal discourses of his day, and also addresses the role of scriptures in Confucian spirituality.